Skip to main content
\(\newcommand{\id}{\mathrm{id}}\) \( \newcommand{\Span}{\mathrm{span}}\) \( \newcommand{\kernel}{\mathrm{null}\,}\) \( \newcommand{\range}{\mathrm{range}\,}\) \( \newcommand{\RealPart}{\mathrm{Re}}\) \( \newcommand{\ImaginaryPart}{\mathrm{Im}}\) \( \newcommand{\Argument}{\mathrm{Arg}}\) \( \newcommand{\norm}[1]{\| #1 \|}\) \( \newcommand{\inner}[2]{\langle #1, #2 \rangle}\) \( \newcommand{\Span}{\mathrm{span}}\)
Mathematics LibreTexts

Section 7.6 Answers

  • Page ID
    29453
  • \( \newcommand{\vecs}[1]{\overset { \scriptstyle \rightharpoonup} {\mathbf{#1}} } \) \( \newcommand{\vecd}[1]{\overset{-\!-\!\rightharpoonup}{\vphantom{a}\smash {#1}}} \)\(\newcommand{\id}{\mathrm{id}}\) \( \newcommand{\Span}{\mathrm{span}}\) \( \newcommand{\kernel}{\mathrm{null}\,}\) \( \newcommand{\range}{\mathrm{range}\,}\) \( \newcommand{\RealPart}{\mathrm{Re}}\) \( \newcommand{\ImaginaryPart}{\mathrm{Im}}\) \( \newcommand{\Argument}{\mathrm{Arg}}\) \( \newcommand{\norm}[1]{\| #1 \|}\) \( \newcommand{\inner}[2]{\langle #1, #2 \rangle}\) \( \newcommand{\Span}{\mathrm{span}}\) \(\newcommand{\id}{\mathrm{id}}\) \( \newcommand{\Span}{\mathrm{span}}\) \( \newcommand{\kernel}{\mathrm{null}\,}\) \( \newcommand{\range}{\mathrm{range}\,}\) \( \newcommand{\RealPart}{\mathrm{Re}}\) \( \newcommand{\ImaginaryPart}{\mathrm{Im}}\) \( \newcommand{\Argument}{\mathrm{Arg}}\) \( \newcommand{\norm}[1]{\| #1 \|}\) \( \newcommand{\inner}[2]{\langle #1, #2 \rangle}\) \( \newcommand{\Span}{\mathrm{span}}\)

    1. \(y_{1} = x\left( 1 − x + \frac{3}{4}x^{2} − \frac{13}{36}x^{3} +\ldots\right) ;\quad y_{2} = y_{1} \ln x + x^{2}\left( 1 − x + \frac{65}{108} x^{2} +\ldots\right)\)

    2. \(y_{1} = x^{−1}\left( 1 − 2x + \frac{9}{2} x^{2} − \frac{20}{3} x^{3} +\ldots\right) ;\quad y_{2} = y_{1} \ln x + 1 − \frac{15}{4} x + \frac{133}{ 18} x^{2} +\ldots \)

    3. \(y_{1} = 1 + x − x^{2} + \frac{1}{3} x^{3} + \dots ;\quad y_{2} = y_{1} \ln x − x\left( 3 − \frac{1}{2} x − \frac{31}{18} x^{2} +\ldots\right)\)

    4. \(y_{1} = x^{1/2}\left( 1 − 2x + \frac{5}{2} x^{2} − 2x^{3} +\ldots\right) ;\quad y_{2} = y_{1} \ln x + x^{3/2}\left( 1 − \frac{9}{4} x + \frac{17}{6} x^{2} +\ldots\right)\)

    5. \(y_{1} = x\left( 1 − 4x + \frac{19}{2} x^{2} − \frac{49}{3} x^{3} +\ldots\right) ;\quad y_{2} = y_{1} \ln x + x^{2}\left( 3 − \frac{43}{4} x + \frac{208}{9} x^{2} +\ldots\right)\)

    6. \(y_{1} = x^{−1/3}\left( 1 − x + \frac{5}{6} x^{2} − \frac{1}{2} x^{3} +\ldots\right) ;\quad y_{2} = y_{1} \ln x + x^{2/3}\left( 1 − \frac{11}{12} x + \frac{25}{36} x^{2} +\ldots\right)\)

    7. \(y_{1} = 1 − 2x + \frac{7}{4} x^{2} − \frac{7}{9} x^{3} +\ldots ;\quad y_{2} = y_{1} \ln x + x\left( 3 − \frac{15}{4} x + \frac{239}{108} x^{2} +\ldots\right)\)

    8. \(y_{1} = x^{−2}\left( 1 − 2x + \frac{5}{2} x^{2} − 3x^{3} +\ldots\right) ;\quad y_{2} = y_{1} \ln x + \frac{3}{4} − \frac{13}{6} x +\ldots \)

    9. \(y_{1} = x^{−1/2}\left( 1 − x + \frac{1}{4} x^{2} + \frac{1}{18} x^{3} +\ldots\right) ;\quad y_{2} = y_{1} \ln x + x^{1/2}\left( \frac{3}{2} − \frac{13}{16} x + \frac{1}{54} x^{2} +\ldots\right)\)

    10. \(y_{1} = x^{−1/4}\left( 1 − \frac{1}{4} x − \frac{7}{32} x^{2} + \frac{23}{384}x^{3} +\ldots\right) ;\quad y_{2} = y_{1} \ln x + x^{3/4}\left( \frac{1}{4} + \frac{5}{64}x − \frac{157}{2304}x^{2} +\ldots\right)\)

    11. \(y_{1} = x^{−1/3}\left( 1 − x + \frac{7}{6} x^{2} −\frac{23}{18} x^{3} +\ldots\right) ;\quad y_{2} = y_{1} \ln x − x^{5/3}\left( \frac{1}{12} − \frac{13}{108} x\ldots\right)\)

    12. \(y_{1}=x^{1/2}\sum_{n=0}^{\infty}\frac{(-1)^{n}}{(n!)^{2}}x^{n};\quad y_{2}=y_{1}\ln x-2x^{1/2}\sum_{n=1}^{\infty}\frac{(-1)^{n}}{(n!)^{2}}\left(\sum_{j=1}^{n}\frac{1}{j} \right)x^{n}\)

    13. \(y_{1}=x^{1/6}\sum_{n=0}^{\infty}\left(\frac{2}{3}\right)^{n}\frac{\prod_{j=1}^{n}(3j+1)}{n!}x^{n};\quad y_{2}=y_{1}\ln x-x^{1/6}\sum_{n=1}^{\infty}\left(\frac{2}{3}\right)^{n}\frac{\prod_{j=1}^{n}(3j+1)}{n!}\left(\sum_{j=1}^{n}\frac{1}{j(3j+1)} \right)x^{n}\)

    14. \(y_{1}=x^{2}\sum_{n=0}^{\infty}(-1)^{n}(n+1)^{2}x^{n};\quad y_{2}=y_{1}\ln x-2x^{2}\sum_{n=1}^{\infty}(-1)^{n}n(n+1)x^{n}\)

    15. \(y_{1}=x^{3}\sum_{n=0}^{\infty}2^{n}(n+1)x^{n};\quad y_{2}=y_{1}\ln x-x^{3}\sum_{n=1}^{\infty}2^{n}nx^{n}\)

    16. \(y_{1}=x^{1/5}\sum_{n=0}^{\infty}\frac{(-1)^{n}\prod_{j=1}^{n}(5j+1)}{125^{n}(n!)^{2}}x^{n};\quad y_{2}=y_{1}\ln x-x^{1/5}\sum_{n=1}^{\infty}\frac{(-1)^{n}\prod_{j=1}^{n}(5j+1)}{125^{n}(n!)^{2}}\left(\sum_{j=1}^{n}\frac{5j+2}{j(5j+1)} \right)x^{n}\)

    17. \(y_{1}=x^{1/2}\sum_{n=0}^{\infty}\frac{(-1)^{n}\prod_{j=1}^{n}(2j-3)}{4^{n}n!}x^{n};\quad y_{2}=y_{1}\ln x+3x^{1/2}\sum_{n=1}^{\infty}\frac{(-1)^{n}\prod_{j=1}^{n}(2j-3)}{4^{n}n!}\left(\sum_{j=1}^{n}\frac{1}{j(2j-3)} \right)x^{n}\)

    18. \(y_{1}=x^{1/3}\sum_{n=0}^{\infty}\frac{(-1)^{n}\prod_{j=1}^{n}(6j-7)^{2}}{81^{n}(n!)^{2}}x^{n};\quad y_{2}=y_{1}\ln x+14x^{1/3}\sum_{n=1}^{\infty}\frac{(-1)^{n}\prod_{j=1}^{n}(6j-7)^{2}}{81^{n}(n!)^{2}}\left(\sum_{j=1}^{n}\frac{1}{j(6j-7)} \right)x^{n}\)

    19. \(y_{1}=x^{2}\sum_{n=0}^{\infty}\frac{(-1)^{n}\prod_{j=1}^{n}(2j+5)}{(n!)^{2}}x^{n};\quad y_{2}=y_{1}\ln x-2x^{2}\sum_{n=1}^{\infty}\frac{(-1)^{n}\prod_{j=1}^{n}(2j+5)}{(n!)^{2}}\left(\sum_{j=1}^{n}\frac{j+5}{j(2j+5)} \right)x^{n}\)

    20. \(y_{1}=\frac{1}{x}\sum_{n=0}^{\infty}\frac{(2)^{n}\prod_{j=1}^{n}(2j-1)}{n!}x^{n};\quad y_{2}=y_{1}\ln x+\frac{1}{x}\sum_{n=1}^{\infty}\frac{(2)^{n}\prod_{j=1}^{n}(2j-1)}{n!}\left(\sum_{j=1}^{n}\frac{1}{j(2j-1)} \right)x^{n}\)

    21. \(y_{1}=\frac{1}{x}\sum_{n=0}^{\infty}\frac{(-1)^{n}\prod_{j=1}^{n}(2j-5)}{n!}x^{n};\quad y_{2}=y_{1}\ln x+\frac{5}{x}\sum_{n=1}^{\infty}\frac{(-1)^{n}\prod_{j=1}^{n}(2j-5)}{n!}\left(\sum_{j=1}^{n}\frac{1}{j(2j-5)} \right)x^{n}\)

    22. \(y_{1}=x^{2}\sum_{n=0}^{\infty}\frac{(-1)^{n}\prod_{j=1}^{n}(2j+3)}{2^{n}n!}x^{n};\quad y_{2}=y_{1}\ln x-3x^{2}\sum_{n=1}^{\infty}\frac{(-1)^{n}\prod_{j=1}^{n}(2j+3)}{2^{n}n!}\left(\sum_{j=1}^{n}\frac{1}{j(2j+3)} \right)x^{n}\)

    23. \(y_{1} = x^{−2}\left( 1 + 3x + \frac{3}{2}^{2} −\frac{1}{2}x^{3} +\ldots\right) ;\quad y_{2} = y_{1} \ln x − 5x^{−1}\left( 1 + \frac{5}{4} x − \frac{1}{4} x^{2} +\ldots\right)\)

    24. \(y_{1} = x^{3} (1 + 20x + 180x^{2} + 1120x^{3} +\ldots );\quad y_{2} = y_{1} \ln x − x^{4}\left( 26 + 324x + 6968 3 x^{2} +\ldots\right)\)

    25. \(y_{1} = x\left( 1 − 5x + \frac{85}{4}x^{2} − \frac{3145}{36} x^{3} +\ldots\right) ;\quad y_{2} = y_{1} \ln x + x^{2}\left( 2 − \frac{39}{4} x + \frac{4499}{108}x^{2} +\ldots\right)\)

    26. \(y_{1} = 1 − x + \frac{3}{4}x^{2} − \frac{7}{12}x^{3} +\ldots ;\quad y_{2} = y_{1} \ln x + x\left( 1 − \frac{3}{4} x + \frac{5}{9} x^{2} +\ldots\right)\)

    27. \(y_{1} = x^{−3} (1 + 16x + 36x^{2} + 16x^{3} +\ldots );\quad y_{2} = y_{1} \ln x − x^{−2}\left( 40 + 150x + \frac{280}{3}x^{2} +\ldots\right)\)

    28. \(y_{1}=x\sum_{m=0}^{\infty}\frac{(-1)^{m}}{2^{m}m!}x^{2m};\quad y_{2}=y_{1}\ln x-\frac{x}{2}\sum_{m=1}^{\infty}\frac{(-1)^{m}}{2^{m}m!}\left(\sum_{j=1}^{\infty}\frac{1}{j} \right)x^{2m}\)

    29. \(y_{1}=x^{2}\sum_{m=0}^{\infty}(-1)^{m}(m+1)x^{2m};\quad y_{2}=y_{1}\ln x-\frac{x^{2}}{2}\sum_{m=1}^{\infty}(-1)^{m}mx^{2m}\)

    30. \(y_{1}=x^{1/2}\sum_{m=0}^{\infty}\frac{(-1)^{m}}{4^{m}m!}x^{2m};\quad y_{2}=y_{1}\ln x-\frac{x^{1/2}}{2}\sum_{m=1}^{\infty}\frac{(-1)^{m}}{4^{m}m!}\left(\sum_{j=1}^{m}\frac{1}{j} \right)x^{2m}\)

    31. \(y_{1}=x\sum_{m=0}^{\infty}\frac{(-1)^{m}\prod_{j=1}^{m}(2j-1)}{2^{m}m!}x^{2m};\quad y_{2}=y_{1}\ln x+\frac{x}{2}\sum_{m=1}^{\infty}\frac{(-1)^{m}\prod_{j=1}^{m}(2j-1)}{2^{m}m!}\left(\sum_{j=1}^{m}\frac{1}{j(2j-1)} \right)x^{2m}\)

    32. \(y_{1}=x^{1/2}\sum_{m=0}^{\infty}\frac{(-1)^{m}\prod_{j=1}^{m}(4j-1)}{8^{m}m!}x^{2m};\quad y_{2}=y_{1}\ln x+\frac{x^{1/2}}{2}\sum_{m=1}^{\infty}\frac{(-1)^{m}\prod_{j=1}^{m}(4j-1)}{8^{m}m!}\left(\sum_{j=1}^{m}\frac{1}{j(4j-1)} \right)x^{2m}\)

    33. \(y_{1}=x\sum_{m=0}^{\infty}\frac{(-1)^{m}\prod_{j=1}^{m}(2j+1)}{2^{m}m!}x^{2m};\quad y_{2}=y_{1}\ln x-\frac{x}{2}\sum_{m=1}^{\infty}\frac{(-1)^{m}\prod_{j=1}^{m}(2j+1)}{2^{m}m!}\left(\sum_{j=1}^{m}\frac{1}{j(2j+1)} \right)x^{2m}\)

    34. \(y_{1}=x^{-1/4}\sum_{m=0}^{\infty}\frac{(-1)^{m}\prod_{j=1}^{m}(8j-13)}{(32)^{m}m!}x^{2m};\quad y_{2}=y_{1}\ln x+\frac{13}{2}x^{-1/4}\sum_{m=1}^{\infty}\frac{(-1)^{m}\prod_{j=1}^{m}(8j-13)}{(32)^{m}m!}\left(\sum_{j=1}^{m}\frac{1}{j(8j-13)} \right)x^{2m}\)

    35. \(y_{1}=x^{1/3}\sum_{m=0}^{\infty}\frac{(-1)^{m}\prod_{j=1}^{m}(3j-1)}{9^{m}m!}x^{2m};\quad y_{2}=y_{1}\ln x+\frac{x^{1/3}}{2}\sum_{m=1}^{\infty}\frac{(-1)^{m}\prod_{j=1}^{m}(3j-1)}{9^{m}m!}\left(\sum_{j=1}^{m}\frac{1}{j(3j-1)} \right)x^{2m}\)

    36. \(y_{1}=x^{1/2}\sum_{m=0}^{\infty}\frac{(-1)^{m}\prod_{j=1}^{m}(4j-3)(4j-1)}{4^{m}(m!)^{2}}x^{2m};\quad y_{2}=y_{1}\ln x+x^{1/2}\sum_{m=1}^{\infty}\frac{(-1)^{m}\prod_{j=1}^{m}(4j-3)(4j-1)}{4^{m}(m!)^{2}}\left(\sum_{j=1}^{m}\frac{8j-3}{j(4j-3)(4j-1)} \right)x^{2m}\)

    37. \(y_{1}=x^{5/3}\sum_{m=0}^{\infty}\frac{(-1)^{m}}{3^{m}m!}x^{2m};\quad y_{2}=y_{1}\ln x-\frac{x^{5/3}}{2}\sum_{m=1}^{\infty}\frac{(-1)^{m}}{3^{m}m!}\left(\sum_{j=1}^{m}\frac{1}{j} \right)x^{2m}\)

    38. \(y_{1}=\frac{1}{x}\sum_{m=0}^{\infty}\frac{(-1)^{m}\prod_{j=1}^{m}(4j-7)}{2^{m}m!}x^{2m};\quad y_{2}=y_{1}\ln x+\frac{7}{2x}\sum_{m=1}^{\infty}\frac{(-1)^{m}\prod_{j=1}^{m}(4j-7)}{2^{m}m!}\left(\sum_{j=1}^{m}\frac{1}{j(4j-7)} \right)x^{2m}\)

    39. \(y_{1} = x^{−1}\left( 1 −\frac{3}{2}x^{2} + \frac{15}{8}x^{4} −\frac{35}{16}x^{6} +\ldots\right) ;\quad y_{2} = y_{1} \ln x + x\left(\frac{1}{4} − \frac{13}{32}x^{2} + \frac{101}{192}x^{4} +\ldots\right)\)

    40. \(y_{1} = x\left( 1 −\frac{1}{2}x^{2} +\frac{1}{8}x^{4} −\frac{1}{48}x^{6}+\ldots\right);\quad y_{2} = y_{1} \ln x + x^{3}\left(\frac{1}{4} − \frac{3}{32}x^{2}+ \frac{11}{576}x^{4} +\ldots\right)\)

    41. \(y_{1} = x^{−2}\left(1 −\frac{3}{4}x^{2} −\frac{9}{64}x^{4} −\frac{25}{256}x^{6} +\ldots\right) ;\quad y_{2} = y_{1} \ln x + \frac{1}{2} − \frac{21}{128}x^{2} − \frac{215}{1536}x^{4} +\ldots \)

    42. \(y_{1} = x^{−3}\left( 1 −\frac{17}{8}x^{2} +\frac{85}{256}x^{4} − \frac{85}{18432}x^{6} +\ldots\right) ;\quad y_{2} = y_{1} \ln x + x^{−1}\left( \frac{25}{8} − \frac{471}{512} x^{2} + \frac{1583}{110592} x^{4} +\ldots\right)\)

    43. \(y_{1} = x^{−1}\left( 1 −\frac{3}{4}x^{2} + \frac{45}{64}x^{4} − \frac{175}{256}x^{6} +\ldots\right) ;\quad y_{2} = y_{1} \ln x − x\left( \frac{1}{4} − \frac{33}{128} x^{2} + \frac{395}{1536}x^{4} +\ldots\right)\)

    44. \(y_{1} = \frac{1}{x} ;\quad y_{2} = y_{1} \ln x − 6 + 6x − \frac{8}{3} x^{2}\)

    45. \(y_{1}=1-x;\quad y_{2}=y_{1}\ln x+4x\)

    46. \(y_{1}=\frac{(x-1)^{2}}{x};\quad y_{2}=y_{1}\ln x+3-3x+2\sum_{n=2}^{\infty}\frac{1}{n(n^{2}-1)}x^{n}\)

    47. \(y_{1}=x^{1/2}(x+1)^{2};\quad y_{2}=y_{1}\ln x-x^{3/2}\left(3+3x+2\sum_{n=2}^{\infty}\frac{(-1)^{n}}{n(n^{2}-1)}x^{n} \right)\)

    48. \(y_{1}=x^{2}(1-x)^{3};\quad y_{2}=y_{1}\ln x+x^{3}\left(4-7x+\frac{11}{3}x^{2}-6\sum_{n=3}^{\infty}\frac{1}{n(n-2)(n^{2}-1)}x^{n} \right)\)

    49. \(y_{1}=x-4x^{3}+x^{5};\quad y_{2}=y_{1}\ln x+6x^{3}-3x^{5}\)

    50. \(y_{1}=x^{1/3}\left(1-\frac{1}{6}x^{2}\right) ;\quad y_{2}=y_{1}\ln x+x^{7/3}\left(\frac{1}{4}-\frac{1}{12}\sum_{m=1}^{\infty}\frac{1}{6^{m}m(m+1)(m+1)!}x^{2m} \right)\)

    51. \(y_{1}=(1+x^{2})^{2};\quad y_{2}=y_{1}\ln x-\frac{3}{2}x^{2}-\frac{3}{2}x^{4}+\sum_{m=3}^{\infty}\frac{(-1)^{m}}{m(m-1)(m-2)}x^{2m}\)

    52. \(y_{1}=x^{-1/2}\left(1-\frac{1}{2}x^{2}+\frac{1}{32}x^{4}\right);\quad y_{2}=y_{1}\ln x+x^{3/2}\left(\frac{5}{8}-\frac{9}{128}x^{2}+\sum_{m=2}^{\infty}\frac{1}{4^{m+1}(m-1)m(m+1)(m+1)!}x^{2m} \right)\)

    56. \(y_{1}=\sum_{m=0}^{\infty}\frac{(-1)^{m}}{4^{m}(m!)^{2}}x^{2m};\quad y_{2}=y_{1}\ln x-\sum_{m=1}^{\infty}\frac{(-1)^{m}}{4^{m}(m!)^{2}}\left(\sum_{j=1}^{m}\frac{1}{j} \right)x^{2m}\)

    58. \(\frac{x^{1/2}}{1+x};\quad \frac{x^{1/2}\ln x}{1+x}\)

    59. \(\frac{x^{1/3}}{3+x};\quad \frac{x^{1/3}\ln x}{3+x}\)

    60. \(\frac{x}{2-x^{2}};\quad \frac{x\ln x}{2-x^{2}}\)

    61. \(\frac{x^{1/3}}{1+x^{2}};\quad \frac{x^{1/4}\ln x}{1+x^{2}}\)

    62. \(\frac{x}{4+3x};\quad \frac{x\ln x}{4+3x}\)

    63. \(\frac{x^{1/2}}{1+3x+x^{2}};\quad \frac{x^{1/2}\ln x}{1+3x+x^{2}}\)

    64. \(\frac{x}{(1-x)^{2}};\quad \frac{x\ln x}{(1-x)^{2}}\)

    65. \(\frac{x^{1/3}}{1+x+x^{2}};\quad \frac{x^{1/3}\ln x}{1+x+x^{2}}\)